Evaluation of the performance of the Family Health Support Center - Mara Dayane Alves Ribeiro; Euriene Maria Araújo Bezerra; Mariana Souza Costa; Carlos Eduardo Castelo Branco; João Dutra Araújo Neto; Ana Karine Figueiredo Moreira; Marcelo de Carvalho Filgueiras (Universidade de Fortaleza, 2014)
Objective: To evaluate the performance of the Family Health Support Center (NASF) through the knowledge and evaluation of services by professionals of the Family Health Strategy (FHS). Methods: Quantitative descriptive study conducted in 2012 with 10 FHS linked to NASF, District 1, Parnaíba - PI - Brazil, where 76 professionals were interviewed using a questionnaire on the characterization of the professional, their knowledge regarding the NASF activities and the evaluation of services provided by the NASF team. The data were divided into categories, grouped and analyzed using SPSS 19.0. Results: In the evaluation of the NASF performance by the members of the FHS, 42% (n=32) considered the service very important, 59.0% (n= 5) of the members were satisfied, 54.0% (n=41) rated the service as accessible to the population, and 90% (n=68) of interviewees recognized which professionals make up the NASF team, highlighting the physiotherapist and the physical educator. Conclusion: It is concluded that the FHS have information regarding the structure of the NASF, pointing the service as very important. Additionally, they are satisfied with the activities performed and rate the service as accessible to the population, which is informed by NASF about their rights in public health. doi:10.5020/18061230.2014.p224